Genetics of Cerebral Vasospasm - Travis R. Ladner; Scott L. Zuckerman; J Mocco (Neurology Research International)
Cerebral vasospasm (CV) is a major source of morbidity and mortality in aneurysmal subarachnoid hemorrhage (aSAH). It is thought that an inflammatory cascade initiated by extravasated blood products precipitates CV, disrupting vascular smooth muscle cell function of major cerebral arteries, leading to vasoconstriction. Mechanisms of CV and modes of therapy are an active area of research. Understanding the genetic basis of CV holds promise for the recognition and treatment for this devastating neurovascular event. In our review, we summarize the most recent research involving key areas within the genetics and vasospasm discussion: (1) Prognostic role of genetics—risk stratification based on gene sequencing, biomarkers, and polymorphisms; (2) Signaling pathways—pinpointing key inflammatory molecules responsible for downstream cellular signaling and altering these mediators to provide therapeutic benefit; and (3) Gene therapy and gene delivery—using viral vectors or novel protein delivery methods to overexpress protective genes in the vasospasm cascade.